Co-operation, Contestation and Complexity in Post-Conflict Security Sector Reform. Issue 1 (1st January 2019) - Ansorg, Nadine; Gordon, Eleanor
ABSTRACT: Security Sector Reform (SSR) remains a key feature of peacebuilding interventions and is usually undertaken by a state alongside national and international partners. External actors engaged in SSR tend to follow a normative agenda that often has little regard for the context in post-conflict societies. Despite recurrent criticism, SSR practices of international organisations and bilateral donors often remain focused on state institutions, and often do not sufficiently attend to alternative providers of security or existing normative frameworks of security. This article provides a critical overview of existing research and introduces the special issue on 'Co-operation, Contestation and Complexity in Post-Conflict Security Sector Reform'. We explore three aspects that add an important piece to the puzzle of what constitutes effective SSR. First, the variation of norm adoption, norm contestation and norm imposition in post-conflict countries that might explain the mixed results in terms of peacebuilding. Second, the multitude of different security actors within and beyond the state which often leads to multiple patterns of co-operation and contestation within reform programmes. And third, how both the multiplicity of and tension between norms and actors further complicate efforts to build peace or, as complexity theory would posit, influence the complex and non-linear social system that is the conflict-affected environment.